ANALISIS TEKNIK CETAK TINGGI SEBAGAI MEDIA DUPLIKASI PADA POSTER KRITIK LINGKUNGAN - sigit purnomo adi (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2021)
In this research the author emphasizes how relief print techniques as a medium for duplication in propaganda poster works are able to present artistic beauty that has distinctive characteristics and is also able to provide awareness to those who see it. The reason the writer is interested in relief print techniques as a means of duplicating propaganda posters is because if you look at the history of relief print, its role wasvery important during the struggle, especially as a medium for duplicating posters of the struggle. Until now, relief print has also been used as a media for duplicating environmental criticism posters to awaken and as a means of education about the importance of protecting this environment. This writing aims to explore further about high printing techniques as a medium for duplication of environmental criticismpropaganda posters as a form of awareness and education about the environment, it turns out that graphic art is not only a form of art that has aesthetic value, but can also be a medium for duplication. The results of this paper are expected to be able to provide benefits in order to enrich the repertoire of graphic arts, especially relief print techniques.